Analysis of the key drivers affecting the development of small and medium sports businesses - Salehipour, Mojgan; Najafabadipour, Zahra; Mohammadi, Samira; Shohani, Mohammadhosein (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to analyze the key drivers affecting the development of small and medium-sized sports businesses. The study employed thematic analysis and a mixed-method approach (qualitative and quantitative), collecting data through interviews, library research, and document evaluation. A judgmental sampling method was used to select 17 participants for the qualitative part, including university professors, researchers, and sports business managers, based on their expertise and job history. Data analysis involved a three-stage coding process, with reliability ensured through coding agreement measures. For the quantitative part, a sample of 384 individuals was selected from employees of sports organizations using Cochran's formula. Based on the findings, the key drivers of sports business development include development policies, infrastructure, technical platforms, organizational frameworks, marketing indicators, strategic agility, and individual capabilities. Focusing on these categories can significantly propel the growth and sustainability of sports businesses. By aligning strategic efforts across these areas, sports organizations can enhance their competitive edge and adapt more effectively to the rapidly changing dynamics of the sports industry.